Penambahan Ekstrak Ranting Karamunting (Rhodomyrtus Temenosa) Sebagai Inhibitor Alami Pada Baja AISI 1040 - Yanti, Lisda; Darma, Daffa Irsyad; Rifani, Muhammad; Tajalla, Gusti Umindya Nur; Awali, Jatmoko; Mohd, Yusairie; Triana, Yunita (LPPM ITK, 2023)
In this study, Karamunting twig extract (Rhodomystus tementosa) was used as a natural inhibitor on AISI 1040 steel. Based on the results of functional group analysis, it was confirmed that the compounds found in Karamunting twig extract are tannins and flavonoids. Electrochemical analysis using the potentiodynamic method showed the lowest corrosion rate at 300 ppm inhibitor concentration, with a corrosion rate of 2.881 mm/yr with an inhibition efficiency of 76.732%. Furthermore, the EIS test showed the highest inhibition efficiency at a concentration of 300 ppm, with a value of 66.720%.